Cerami, the Home of the Confraternities: Types of Communitas, Passionate Paths and Festive Customs - Ginex , Maurilio (E|C, 2024)
Cerami is a town of the Nebrodi chain in Sicily and represents the country of the brotherhoods, as every aspect of its festive calendar revolves around the roles that the latter play. A brotherhood is a clear example of ritual communitas and to enter into it a rite of passage takes place. The brotherhoods are opposed during the profane time but in a sacred time, therefore during the religious holidays, they collaborate.